Impact of excessive environmental information disclosure on stock price crash risk - Guoping Dong; Guifen Ma (PLoS ONE, 2025)
With the deepening of carbon peak and carbon neutrality (“dual carbon”) initiatives, corporate responsibility for environmental information disclosure has become imperative. However, due to imperfect laws and regulations, companies may have incentives to over-disclose environmental information, which could trigger stock price crashes. This study investigates the behavior of excessive environmental information disclosure among A-share listed companies in China. Using a sample of A-share firms that published social responsibility reports from 2015 to 2023, we employ threshold effect and quantile regression models to verify the presence of “greenwashing” components in environmental textual disclosures. A panel fixed-effects model is further adopted to examine the potential impact of excessive environmental information disclosure on stock price crash risk. The findings reveal that corporate environmental disclosures contain non-substantive, embellished content-indicative of greenwashing-and that such behavior significantly exacerbates stock price crash risk, particularly in manufacturing industries. The mechanism lies in the fact that excessive textual disclosure reduces information quality and transparency, thereby amplifying irrational investment behaviors. Conversely, effective environmental disclosure practices are shown to mitigate crash risk. Further analysis demonstrates that reducing ownership concentration, increasing managerial shareholding, and enhancing the role of independent directors in corporate governance can improve the quality of environmental disclosure and curb over-disclosure. This study provides a novel analytical perspective on environmental textual disclosure and offers practical insights for guiding rational investor decision-making.